语用小品词“呢”的位置分布与互动功能研究 - Huo Xingyu; Li Zhenzhen (Sinolingua: Journal of Chinese Studies, 2025)
Based on DMC natural spoken corpus, we study the pragmatic particle "ne" in Chinese, focusing on its location distribution and interactive function. The results show that in the specific position of "sequence initiation + middle of the round", the small word "ne" mainly assumes the function of statement, and is less used to express questions. In addition, we also find that the "ne" of this position plays multiple roles in interactive communication. First, it can be used as a marker to reflect the inner thoughts of the speaker, thus weakening the influence of objective behavior to a certain extent. Secondly, it can weaken the interrogative tone and make the question point more to the speaker himself. Finally, by reducing its own weight, it can effectively highlight the importance of subsequent information. These findings are of great significance for us to further understand and use the pragmatic particle words in Chinese.